Analyzing The Use Of Discourse Markers In EFL Classroom Interactions: A Qualitative Study At Bali International Language Center - Lindawati, Ni Putu; Asriyani, Retny; Anggayana, I Wayan Agus (International Journal of Linguistics and Discourse Analytics, 2024)
Discourse markers are essential for effective communication, serving to structure and manage interactions in both native and non-native language contexts. Despite their significance, there is a noticeable gap in the literature regarding their specific functions within English as a Foreign Language (EFL) settings and how these functions align with theoretical frameworks versus practical classroom applications. This study aims to address this gap by exploring the use of discourse markers in an EFL classroom setting and assessing their impact on communication. The study’s primary objective is to analyze the utilization of discourse markers in EFL classroom interactions, identify patterns of their usage, and evaluate their effectiveness in facilitating communication between students and teachers. Employing a qualitative research design, the study involved detailed observations of one randomly selected class at Bali International Language Center (BILCEN). Data were collected through audio recordings of classroom interactions, which were transcribed and analyzed thematically. Instruments used for data collection included observation protocols and transcription software. The findings indicate that discourse markers were frequently used to manage conversational flow, signal transitions, and link ideas, playing a crucial role in maintaining coherence and promoting smoother communication. However, instances of overuse or incorrect usage occasionally led to misunderstandings among students. In conclusion, this study highlights the importance of discourse markers in enhancing EFL classroom interactions and suggests that focused instruction on these markers can significantly improve students' communicative competence. By bridging the gap between theoretical understanding and practical implementation, the research offers valuable insights for educators aiming to enhance oral communication skills in EFL contexts